'On the tools': the physical work of building and renovating houses in Perth, Western Australia. - Moore, Philip (Routledge, 2013)
The construction industry as a workplace is commonly seen as problematic for a number of reasons, including its worrying health and safety record, the instability of its workforce, and the poorly regulated nature of the sector. It is surprising therefore, that the sector and its working practices remain so under-theorised. Now though, there is a growing interest in and awareness of the utility of an ethnographic approach to the construction industry. Ethnographic Research in the Construction Industry draws together in one volume a set of expert contributions which demonstrate how social science perspectives, rooted in ethnographic research on construction sites and with construction workers themselves, can generate fresh insights into the social, cultural and material ways that the industry and conditions of work in it are experienced and played out. Each chapter develops discussion on the basis of an ethnographic case study to examine how theoretically informed ethnographic research can help us understand industry problems, and can challenge common perceptions of the construction industry. This book will be of interest to students and scholars of anthropology, sociology, geography and organization studies, as well as those from the built environment and related applied fields.